2021
DOI: 10.3390/cancers13163941
|View full text |Cite
|
Sign up to set email alerts
|

Bacitracin and Rutin Regulate Tissue Factor Production in Inflammatory Monocytes and Acute Myeloid Leukemia Blasts

Abstract: Aberrant expression of tissue factor (TF) by transformed myeloblasts and inflammatory monocytes drives coagulation activation in acute myeloid leukemia (AML). Although regulation of TF procoagulant activity (PCA) involves thiol-disulfide exchange reactions, the specific role of protein disulfide isomerase (PDI) and other thiol isomerases in AML-associated TF biology is unclear. THP1 cells and peripheral blood mononuclear cells (PBMCs) from healthy controls or AML patients were analyzed for thiol isomerase-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Our previous work has demonstrated that circulating PDI is associated with increased risks of cancer‐induced thrombosis, 9 along with increased levels of tissue factor 47 . Interestingly, tissue factor is also expressed on the surface of some cancer cells 48 and in this study, we found that both cellular thiol isomerase activity (Figure 2A) and tissue factor‐dependent Factor Xa generation (Figure 4E) was inhibited by zafirlukast in ovarian cancer cells, which would further support exploration of zafirlukast for cancer‐induced thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has demonstrated that circulating PDI is associated with increased risks of cancer‐induced thrombosis, 9 along with increased levels of tissue factor 47 . Interestingly, tissue factor is also expressed on the surface of some cancer cells 48 and in this study, we found that both cellular thiol isomerase activity (Figure 2A) and tissue factor‐dependent Factor Xa generation (Figure 4E) was inhibited by zafirlukast in ovarian cancer cells, which would further support exploration of zafirlukast for cancer‐induced thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bacitracin and quercetin-3-rutinoside (rutin) are two PDI inhibitors. A recent study showed that bacitracin and rutin inhibited LPS induction of TF protein expression and activity in CD14-positive human monocytes and human peripheral blood mononuclear cells (PBMCs), respectively 88 . In addition, rutin reduced LPS induction of TF mRNA in human PBMCs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…2A ), as assessed by a previously described chromogenic Xa generation endpoint assay. 9 High dosages of argatroban were required to maintain the activated partial thromboplastin time within the upper therapeutic target range ( Fig. 2B ).…”
Section: Case Presentationmentioning
confidence: 99%